Human Resource Development through Education and Training: Literature Review and Applications in Organizations (International Journal of Scientific Research and Management (IJSRM), 2025)
Improving the quality and competitiveness of organizations can be achieved through developing human resources (HR) through education and training, which are important factors in achieving these goals. In an era of globalization that is increasingly full of competition, organizations must be able to face challenges to continue to grow and adapt to changes that occur rapidly. The method in this research is qualitative. The results of this research are: human resource development through education and training has a significant impact on increasing individual competence and organizational performance, where effective education and training can improve employees’ technical and non-technical skills, which in turn improves productivity and quality of work. With the right program, organizations can ensure employees have the knowledge and abilities to face challenges and adapt to industrial and technological developments, ultimately strengthening the organization’s overall competitiveness. Effective implementation of training programs relies heavily on in-depth needs analysis and selection of training methods that suit organizational goals. Therefore, organizations need to carry out careful planning, choose competent facilitators, and get full support from management to create a conducive climate. In addition, evaluating the impact of training is important to ensure that the program implemented produces results that are in line with the objectives, both in improving employee skills, organizational performance and employee satisfaction. By using various appropriate evaluation tools, organizations can measure the effectiveness of training, make necessary improvements, and ensure that training remains relevant and makes a real contribution to human resource development and achieving the organization’s strategic goals.